Development of functional biomaterials with micro‐ and nanoscale technologies for tissue engineering and drug delivery applications. (18th June 2012) - Bae, Hojae; Chu, Hunghao; Edalat, Faramarz; Cha, Jae Min; Sant, Shilpa; Kashyap, Aditya; Ahari, Amir F.; Kwon, Cheong Hoon; Nichol, Jason W.; Manoucheri, Sam; Zamanian, Behnam; Wang, Yadong; et al.
Abstract Micro‐ and nanotechnologies have emerged as potentially effective fabrication tools for addressing the challenges faced in tissue engineering and drug delivery. The ability to control and manipulate polymeric biomaterials at the micron and nanometre scale with these fabrication techniques has allowed for the creation of controlled cellular environments, engineering of functional tissues and development of better drug delivery systems. In tissue engineering, micro‐ and nanotechnologies have enabled the recapitulation of the micro‐ and nanoscale detail of the cell's environment through controlling the surface chemistry and topography of materials, generating 3D cellular scaffolds and regulating cell–cell interactions. Furthermore, these technologies have led to advances in high‐throughput screening (HTS), enabling rapid and efficient discovery of a library of materials and screening of drugs that induce cell‐specific responses. In drug delivery, controlling the size and geometry of drug carriers with micro‐ and nanotechnologies have allowed for the modulation of parametres such as bioavailability, pharmacodynamics and cell‐specific targeting. In this review, we introduce recent developments in micro‐ and nanoscale engineering of polymeric biomaterials, with an emphasis on lithographic techniques, and present an overview of their applications in tissue engineering, HTS and drug delivery. Copyright © 2012 John Wiley & Sons, Ltd.